Effect of Non-Pharmachological Therapies For Pregnant Women with Mental Disorder: A Narrative Review: Effect of Non-Pharmachological Therapies For Pregnant Women with Mental Disorder: A Narrative Review - Hidayati, Nur Oktavia; Nuraeni, Aan; Nurhidayah, Ikeu; Rhamelani, Putri; Nurjanah, Lilis Siti; Yani, Pebri; Regita, Yasmina Dwi (Jurnal Surya Medika (JSM), 2024)
Purpose: To determine the effectiveness of non-pharmacological interventions given to pregnant women with mental disorders. Methodology: The method used was a narrative review. Articles searched using PubMed, Science Direct and EBSCO databases. Eight articles were obtained as the final number of articles suitable for review. Findings: Of the eight articles were obtained, all used RCTs. Based on the eight articles that have been analysed, there are eight interventions, namely Spiritual Integrated Cognitive-Behavioural Educational Intervention, Cognitive Behavioural Therapy, Mindfulness-Based Childbirth and Parenting Program, Mindfulness-Based Cognitive Therapy, Bright Light Therapy, Transcranial Magnetic Stimulation Intervention, Group-Based Multicomponent Treatment, and The Mindful-moms Training. Contribution: Some of the interventions found can be used in the area of maternity nursing, especially for pregnant women and in the area of psychiatric nursing which focuses on mental disorders.